Oneroid syndrome: a rare form of psychosis - A., Chamelee; Selvamani, Iniyan; Nambi, Shanthi (International Journal of Research in Medical Sciences, 2019)
Oneiroid syndrome (OS) or dream-like fantastic delusional derangement of consciousness, is characterized by a kaleidoscopic quality of psychopathological experiences, wherein reality, illusions and hallucinations are merged into one. This syndrome is an uncommon psychiatric condition, which hardly finds any mention in psychiatric literature. Also, does not find a place in the current diagnostic systems. Here, we describe a rare case of oneroid syndrome in a young adult who presented to our department and who responded well to anti psychotics.